2013
DOI: 10.1007/s10895-013-1175-0
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Homogeneous Time-Resolved Fluoroimmunoassay for Carcinoembryonic Antigen Based on Water-Soluble Quantum Dots

Abstract: Quantum dots are not widely used in clinical diagnosis. However, the homogeneous time-resolved fluorescence assay possesses many advantages over current methods for the detection of carcinoembryonic antigen (CEA), a primary marker for many cancers and diseases. Therefore, a novel luminescent terbium chelates- (LTCs) and quantum dots-based homogeneous time-resolved fluorescence assay was developed to detect CEA. Glutathione-capped quantum dots (QDs) were prepared from oil-soluble QDs with a 565 nm emission peak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 52 publications
0
16
0
Order By: Relevance
“…632 To investigate and prove this concept, Liu et al utilized in-house-synthesized Tb-complexes and QDs and demonstrated TG Tb-to-QD FRET homogeneous immunoassays for alpha-fetoprotein (AFP) and carcinoembryonic antigen (CEA) in buffer. 629,630 Extending their applicability to clinical diagnostics and multiplexing, Hildebrandt et al…”
Section: Quantum Dots As Acceptormentioning
confidence: 99%
“…632 To investigate and prove this concept, Liu et al utilized in-house-synthesized Tb-complexes and QDs and demonstrated TG Tb-to-QD FRET homogeneous immunoassays for alpha-fetoprotein (AFP) and carcinoembryonic antigen (CEA) in buffer. 629,630 Extending their applicability to clinical diagnostics and multiplexing, Hildebrandt et al…”
Section: Quantum Dots As Acceptormentioning
confidence: 99%
“…FRET immunoassays have been developed with QD-donors [12][13][14][15][16][17][18][19] as well as QD-acceptors. 11,[20][21][22][23][24] The latter case is of particular interest, because these FRET assays used Tb-complexes as donors, whose extremely long excited-state lifetimes allow for time-gated detection and a concomitant suppression of directly excited QD PL and autofluorescence background. 3,8,9 Such Tb-to-QD energy transfer systems have been shown to follow FRET theory 25,26 and were successfully used in various homogeneous FRET biosensing applications, ranging from molecular rulers, 27,28 over nucleic acid detection and enzyme kinetics, 29,30 to molecular logic gates.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, alternative methods for in situ detection were proposed, such as those replacing fluorescent-based reporters for quantum dots that are directly conjugated in primary antibodies. Quantum dots allow for a higher number of probes to be detected at the same tissue because of reduced spectral overlap (Byers and Hitchman, 2011;Chan et al, 2005;Chen et al, 2013;Dixon et al, 2015;Krenacs et al, 2010;Mansfield, 2017;Prost et al, 2016;Sweeney et al, 2008;Tholouli et al, 2008;Wu et al, 2003;Xu et al, 2013), however, quantum dots and other similar techniques require expensive, specialized equipment.…”
Section: Introductionmentioning
confidence: 99%